Programme Selection in Research and Development - Lockett, A. Geoffrey; Gear, Anthony E. (Management Science, 1972)
Mathematical programming as an aid to R & D project portfolio selection has been suggested by many authors, but few practical applications have been reported. This paper discusses some, of the difficulties, associated with the application of the proposed models, and describes procedures for handling these problems. Problem areas considered are: Allowance for future opportunities in multi-period models, Generation of alternative risk-return solutions, Inclusion of projects not completed during the planning period, Comparison of linear and integer programming outputs. In the main, both the problems and methods of solution are clarified by means of numerical examples, and details of a practical case study are given.